Ideas sobre el concepto biológico de población - Berzal de Pedrazzini, M.; Barberà, O. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
The population concept is one of the foremost in biology, and íts comprehension is essential to grasp the genetical and evolutionary aspects of living beings. Nevertheless, school science hardly takes into account the richness arid complexity of the biological concept of population. We have carried out this study with the intention of finding out students' ideas about the population concept (and other concepts related to it such as the species concept) and putting forward some hypotheses to explain the origins of these ideas.